SBT (Composed of Panax ginseng and Aconitum carmichaeli) and Stigmasterol Enhances Nitric Oxide Production and Exerts Curative Properties as a Potential Anti-Oxidant and Immunity-Enhancing Agent - Na-Ra Han; Kyeoung-Cheol Kim; Ju-Sung Kim; Hi-Joon Park; Seong-Gyu Ko; Phil-Dong Moon (MDPI AG, 2022)
Immune dysregulation is a risk factor for several diseases, including infectious diseases. Immunostimulatory agents have been used for the treatment of immune dysregulation, but deleterious adverse effects have been reported. The present study aims to establish the anti-oxidant and immunity-enhancing effects of Sambu-Tang (SBT), composed of Panax ginseng and Aconitum carmichaeli, and stigmasterol (Stig), an active compound of SBT. Immune-related factors were analyzed in RAW264.7 macrophage cells, mouse primary splenocytes, and the serum and spleen of cyclophosphamide-induced immunosuppressed mice. Results showed that the production levels of nitric oxide (NO) and expression levels of inducible NO synthase and heme oxygenase-1 were increased following SBT or Stig treatment in RAW264.7 cells. SBT or Stig increased the production levels of G-CSF, IFN-γ, IL-12, IL-2, IL-6, and TNF-α and induced the activation of NF-κB in RAW264.7 cells. SBT or Stig promoted splenic lymphocyte proliferation and increased splenic NK cell cytotoxic activity. In addition, SBT or Stig enhanced the levels of IFN-γ, IL-12, IL-2, IL-6, or TNF-α in the serum and spleen of the immunosuppressed mice. SBT or Stig increased the superoxide dismutase activity in the spleen. Collectively, SBT and Stig possess anti-oxidant and immunomodulatory activities, so they may be considered effective natural compounds for the treatment of various symptoms caused by immune dysregulation.